Prevalencia de Microfilaria immitis en primates neotropicales en el centro de rescate de fauna silvestre James Brown - Palacios Palacios, Luis Felipe (2025)
The purpose of this research was to determine the prevalence of Microfilaria immitis in neotropical primates at the James Brown Wildlife Rescue Center – The Concord. A non-experimental, descriptive and quantitative study was developed, within this, 15 primates of different species were evaluated, which were subjected to laboratory tests such as the thick drop and confirmatory methods such as the Woo technique, blood smear and the 4Dx kit, for the identification of positive cases of Microfialria immitis. In addition, a complete blood count was performed on the primates to detect clinical findings underlying the presence of the parasite. Finally, a structured survey was conducted with employees of the rescue center to determine the risk factors that predispose to the presence of this pathogen. The results show that there was no prevalence of Microfilaria immitis in the primates evaluated. On the other hand, despite the absence of the parasite, alterations in the parameters of lymphocytes, monocytes, granulocytes, mean corpuscular volume, mean corpuscular hemoglobin and platelet count were observed in the hemogram, which could affect the immune response and hematological function of the primates. Overall, no prevalence of Microfilaria immitis was detected, but hematological alterations and deficiencies in admission protocols could increase vulnerability to this type of infection.